The Influence Of Fanpages Following Instagram On Intention To Transact With Sense Of Brand Community And Brand Love Mediators In Digital Financial Companies - Alfiani, Dewi Fortuna; Fadli, Jul Aidil (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Social media has given consumers the opportunity to speak up for the products or services they sell and consume. In recent years, the social networking site Instagram is one of the most popular social networking sites for consumers. One of the most widely used platforms by companies for Instagram marketing is "Fan page following". This study aims to determine the effect of fan pages following Instagram on transaction intentions with the mediation of sense of brand community and brand love in digital financial companies. The sampling method used purposive sampling with a sample size of 80 respondents. The number of statements given to respondents was 16 statement items. The data were analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM). The results of this study indicate a significant effect of fan pages following on the sense of brand community, a significant effect on fan pages following on brand love, an insignificant effect on the sense of brand community with transaction intention, a significant effect on, a significant effect of brand love on transaction intention, a significant effect on fan pages following on transaction intention, an insignificant mediating effect on the sense of brand community with fan pages following and transaction intention and a significant mediating effect on brand love with fan pages following and transaction intention. Keywords:Fanpage Following, Sense of Brand Community, Brand Love,Transaction Intention